4b-8=1+6-3b-1

Simple and best practice solution for 4b-8=1+6-3b-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4b-8=1+6-3b-1 equation:


Simplifying
4b + -8 = 1 + 6 + -3b + -1

Reorder the terms:
-8 + 4b = 1 + 6 + -3b + -1

Reorder the terms:
-8 + 4b = 1 + 6 + -1 + -3b

Combine like terms: 1 + 6 = 7
-8 + 4b = 7 + -1 + -3b

Combine like terms: 7 + -1 = 6
-8 + 4b = 6 + -3b

Solving
-8 + 4b = 6 + -3b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '3b' to each side of the equation.
-8 + 4b + 3b = 6 + -3b + 3b

Combine like terms: 4b + 3b = 7b
-8 + 7b = 6 + -3b + 3b

Combine like terms: -3b + 3b = 0
-8 + 7b = 6 + 0
-8 + 7b = 6

Add '8' to each side of the equation.
-8 + 8 + 7b = 6 + 8

Combine like terms: -8 + 8 = 0
0 + 7b = 6 + 8
7b = 6 + 8

Combine like terms: 6 + 8 = 14
7b = 14

Divide each side by '7'.
b = 2

Simplifying
b = 2

See similar equations:

| 2x^2+kx^2-2kx-16=0 | | 2x-(x+2)=2x-0.1 | | 6=7x-x+6 | | w*w+9=6w | | 4x+172=180 | | .3T-2.1C-2.3=7.6 | | 5r+4=9(r-3) | | (m/2)-(1/m)=(6m+5/12) | | X^2+6X=34 | | 15x-75=90 | | Y=(15x+10)(15x-2) | | 3(2a-b)-5a= | | 7v+2=0 | | 2x-4x+4=x-3+7 | | 7=3(t-5)-t | | 3x^2-2x-8=448 | | Y=225x^2+120x+20 | | 1.3x+1.6y=.6 | | 15x-150=90 | | -8-2(8n-8)=-6n+8 | | 5x-2x-3=27 | | -76+n=-115 | | 6tx=4+2 | | 5x-6+6/5=14+6/5 | | 3a+8+a-9-2= | | 15=9w | | 10x+34=114 | | (x+2)2=13 | | -13+3x=-52+24 | | 4cos^2(x)+1=3 | | 5x+6+6/5=16+6/5 | | 8p+2=4-10 |

Equations solver categories